Pemberdayaan Petugas Rekam Medis dalam Analisis Kebutuhan SIM Klinik Bagian Registrasi Pasien Di Klinik Prima Husada Bandung - Tedy Hidayat; Nurul Dwi Ariyani; Jajat Sudrajat; Nadia Rizki Pratami; Falaah Abdussalaam; Sani Fitriyani (LPPM Politeknik Piksi Ganesha, 2024)
Based on the community service team's observations, the patient registration process at Prima Husada Clinic still uses manual recording through a register book. This condition results in long registration times because officers have to search for patient data one by one. This community service activity aims to provide assistance to medical records officers in analyzing the needs of a Clinical Management Information System (CMI) in the patient registration section. The activity was carried out for three days with three participants, consisting of two registration officers and one head of medical records. The implementation method included socialization, interactive discussions, and practice in preparing a patient registration flowchart. The evaluation results showed an increase in participant knowledge of 40%, with an average pretest score of 50.00 and a posttest score of 90.00. This activity is expected to help officers understand and analyze the needs of a Clinical Management Information System (SIM Klinik) so that the system designed is in accordance with the clinic's operational needs.